Two new aluminophosphates, IST-1 and IST-2: first examples of a dual templating role of water and methylamine in generating microporous structures - Fernandes, A. (2013)
This study is aimed at exploring the ability of very small sized N-bearing molecules to generate and stabilize microporous aluminophosphates. Two new AlPO4-n materials, called IST-1 and IST-2, have been obtained in aqueous media using, as main template, methylamine (MA), directly added, or generated in situ from methylformamide (MF) degradation. While IST-1 topology proved to be novel, IST-2 appears structurally related to AlPO4-53(A). The obtained materials were characterized by powder XRD, TG/DSC, SEM and solid-state NMR. Tetraalkylammonium (TEA) cations were used as potential co-templates but only MA and water were found incorporated in the pore volumes of both structures, which argues for their true templating role. In IST-1, 13C solid-state NMR studies showed that half of MA species, presumably protonated, is H-bonded to framework oxygens while the other half surprisingly bonds directly to framework Al atoms. 13C NMR showed that only protonated MA occurs in IST-2 channels. TEA+ cations definitely do not play any specific template role. They indirectly favor the crystallization of IST-1 or IST-2 devoid from other crystalline or amorphous side phases, by interacting with part of the Al and P in solution and forming soluble [AlPO4(OH)]–[TEA,HMA] complexes, substantially modifying the compositions of gels precursors to each phase during nucleation and/or growth steps. While both IST-1 and IST-2 crystallize from gels of similar initial compositions, it was demonstrated that the new MA/T ratio (T = Al or P) obtained after in situ complexation was the key parameter that specifically governs the crystallization of each phase.